(untitled) (Jurnal Teknologi (Sciences & Engineering), 2018)
2-D resistivity method has been widely used for aquifer detection, where aquifers are usually made of porous rocks. The aim of this study is to detect the aquifer using 2-D resistivity method and porosity calculation from Archie’s Law. The porosity of the subsurface materials can be known and the porous materials can be easily detected. This study was done at two different locations which are in Selangor and Kelantan. Two lines of 2-D resistivity survey were conducted at each location. The results were correlated with borehole records. Only one borehole was executed at each location near to the 2-D resistivity lines. The saturated zones (1-100 Ωm) that found from the 2-D resistivity results were suspected to be an aquifer, and the zones were validated by the borehole records. Lastly, the porosity was calculated for all 2-D resistivity lines and an imaging was created for each line. A productive sedimentary aquifer should have porosity percentage of >20% and the saturated zone at both study area have porosity percentage of >20% as expected.